Underwater criticism: Derek Walcott and Édouard Glissant - Aguirre Aguirre, Carlos (2025)
The article exposes and problematizes the modulations of submarine criticism in two Caribbean authors: Derek Walcott (1930-2017) and Édouard Glissant (1928-2011). First, it exposes the philosophical-cultural particularities of Caribbean and Antillean criticism that takes up maritime geography as a reflexive, epistemological and transcultural facticity from the postulate of a “submarine unity” by Kamau Brathwaite. Secondly, the text analyzes Walcott’s historical reading of colonialism and his metapoetic strategy in two of his works: the poem The sea is History and his speech when receiving the Nobel Prize for Literature. As a third part, the article focuses on Glissant’s proposal for an archipelagic thought, investigating the heuristic and critical character of the submarine fragment as an epistemological image that forms an important part of the Relation. Finally, he concludes that Walcott and Glissant carry out a critique of colonialism from the underwater openings of the Antillean landscape in order to diagram another type of future historical-cultural imagination.